"Knight of Internationalization": U.N. delegate Charles Malik of Lebanon and U.N. General Assembly Resolution 303 calling for the internationalization of Jerusalem. Issue 5 (20th October 2021) - Ben-Dror, Elad
ABSTRACT: On 9 December 1949, the United Nations General Assembly adopted Resolution 303 calling for the full internationalization of Jerusalem although many had grave doubts about the viability of the plan and a more practical alternative focusing on the holy places was then sitting on the table. This article sheds light on the diplomacy of Charles Malik, Lebanon's U.N. representative, whose tireless efforts were responsible in large measure for the adoption of this resolution.